Wildlife trade at the interface between deeply-rooted animal-based traditional medicine and unregulated harvesting of wild animals in West Africa - Zanvo, Stanislas; Dognimon, Samson; Djagoun, Chabi A. M. S.; Akpatchémè, Jiroux; Azihou, Akomian Fortuné; Djossa, Bruno; Sogbohossou, Etotépé A.; Sinsin, Brice (Frontiers in Conservation Science, 2024)
Local trade remains a data poor component of wildlife crime that must be better understood for more effective combat against the illegal wildlife trade. We assessed the distribution of wildlife markets, diversity of species traded and the extent of the trade chain through spatial analysis of wildlife sale sites and semi-structured interviews with 75 vendors in the 10 largest traditional medicine markets of Benin. GPS coordinates of wildlife markets were used to map their geographic distribution and assess their spatial patterns. We used a generalized linear model to determine the drivers underlying the spatial patterns of wildlife markets. A circular layout was designed to delineate the geographic extent of wildlife trade in terms of supplying sources. We found that wildlife was traded at 121 sale sites in Benin, highly dominated by traditional medicine markets (106 sites). The spatial analysis of markets exhibited an aggregative distribution pattern, and the type of market, the number of stalls in the markets and the municipality status influence significantly the spatial temporality of market distribution. Wildlife trade for traditional medicine affected 268, 96 and 61 bird, mammal and reptile species, respectively, and included species of both high national and global conservation concern. We also found that the national wildlife trade in Benin was supplied from 80% (12/15) West African Economic and Monetary countries, and all the Economic Community of West African States (except Guinea-Bissau) in violation of national laws, CITES, and regional commitments to combat wildlife trafficking (e.g., the West African Strategy for Combatting Wildlife Crime). Our study in Benin is a big step to revealing trade throughout in West Africa. It provides much needed information on wildlife trade structure and driving forces that could help to inform decision-making for better trade regulation and for effective wildlife law enforcement in West Africa. Other studies should do the same to help paint a more complete picture of wildlife trade in West Africa.